Stochastic Models, Statistics and Their Applications (Wrocław, Poland, February 2015) - Steland, Ansgar (Springer, 2015)
This volume presents papers collected on the occasion of the 12th Workshop on Stochastic Models, Statistics and Their Applications, jointly organized by the Insti tute of Mathematics and Computer Science of Wrocław University of Technology, the Institute of Computer Engineering, Control and Robotics, Wrocław University of Technology, and by the Institute of Statistics of RWTH Aachen University. This German series of workshops has been frequently held together with research groups from Poland, i.e. as German–Polish events. It has become more and more interna tional and takes place at Wrocław for the second time....